Analisis Peran Masyarakat Lembang Bau Terhadap Peningkatan Destinasi Wisata Arung Jeram di Kabupaten Tana Toraja - Elgi; Dejusniati Rasinan; Mira Labi Bhandhaso (Yos Soedarso Economic Journal (YEJ), 2024)
This study aims to determine the Role of the Lembang Bau Community in Increasing White Water Rafting Tourism Destinations in Tana Toraja. The methods used in this study are literature studies, questionnaires, and interviews. Data were analyzed using descriptive qualitative analysis. The results of the study indicate that the Lembang Bau Community has a Role in Increasing White Water Rafting Tourism Destinations in Tana Toraja Regency which is assessed well and has met several indicators, attitudes towards tourists, environmental awareness, appreciation for cultural heritage, Participation in tourism development, education and knowledge about tourism, readiness to face change.